Keputusan Membeli Smartphone Ditinjau Dari Harga Diri Mahasiswa Fakultas Hukum Univesitas Medan Area - Jesika Sari Hasibuan; Ananda Kalfin Sitorus; Jesica Tania Sirait; Videllia Sendy Hesela Tarigan; Winida Marpaung (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to determine the relationship between self-esteem and buying decision. The hypothesis proposed in this study stated that there was a positive relationship between self-esteem and buying decision, assuming the higher self-esteem and the higher buying decision, and conversely the lower self-esteem, the lower the buying decision. Subjects used in this students of university area law faculty Workers consisting of 123 people who were selected by using purposive sampling technique. Data were obtained from a scale to measure self-esteem and buying decision. The calculation was performed by means of testing requirements analysis (assumption test) that consists of a test for normality and linearity. Analysis of the data used was performed by Product Moment Analysis through SPSS 17 for Windows. The results of data analysis showed that r = 0.211 and p = 0.010 (p < 0.05), indicating that there was a positive relationship between self-esteem and buying decision. The results of this study indicated that the contribution (R2) given to the buying dicision to variable of self-esteem was 4,4 %, the remaining 95,6 % were affected by other factors not examined. From these results it can be concluded that the hypothesis is acceptable.